Салихов Т.К., Тыныкулов М.К., Салихова Т.С., Берденов Ж.Г. Значимые, репрезентативные и уникальные растительные сообщества проектируемого государственного природного резервата «Бокейорда» Западно-Казахстанской области: Евразийский национальный университет имени Л.Н. Гумилева, Казахстан, г. Астана, e-mail: alikhov_tk@enu.kz; tuatai_76@mail.ru (Eurasian Journal of Ecology, 2017)
This work is devoted to the problems of environmental protection in Kazakhstan by the example ofthe ongoing project, which shows the results of the scientific justification for the projected state naturereserve «Bokeyorda» in the West Kazakhstan region.As a result of the research, the current state of thevegetation cover was studied and the presence of unique and significant plant communities in the territory of the projected state nature reserve «Bokeiord» of the West Kazakhstan region was identified topreserve the habitat of rare and endemic species of biodiversity throughout the region. The studies were carried out within the framework of the project of the Government of the Republic of Kazakhstan and theGlobal Environment Facility of the United Nations Development Program «Conservation and SustainableManagement of Steppe Ecosystems», aimed at increasing steppe ecosystems.The monitoring sites have been bookmarked with the application of their data to the topographicmap and the GPS data on the sites have been recorded. The mapping of the habitats of key plant species, assessment of the impact of negative factors on biological diversity has been carried out. Whereon the basis of the ecosystem analysis and GIS-technologies are identified the most important areas forbiodiversity conservation, the boundaries of the reserve are defined.Given that currently in the West Kazakhstan region there are no specially protected natural areaswith strict protection regime, the organization of a new environmental institution will allow not onlyto ensure the preservation and restoration of the steppe biodiversity of the region, but also to improvesocial and economic conditions through the creation of additional workers Places, development of ecological tourism, etc. To a large extent this will be facilitated by the creation of a large state nature reserve«Bokeyorda» and a complex state nature reserve in the west of the West Kazakhstan region.Key words: plant communities, specially protected natural territories, steppes, biodiversity, flora,habitat, ecosystem.